[F-18]FMPEP-d(2) PET imaging shows age- and genotype-dependent impairments in the availability of cannabinoid receptor 1 in a mouse model of Alzheimer's disease - Jatta S. Takkinen; Francisco R. López-Picón; Anna K. Kirjavainen; Rea Pihlaja; Anniina Snellman; Tamiko Ishizu; Eliisa Löyttyniemi; Olof Solin; Juha O. Rinne; Merja Haaparanta-Solin (ELSEVIER SCIENCE INC, 2022)
Contradictory findings on the role of the type 1 cannabinoid receptor (CB1R) during the pathogenesis of Alzheimer's disease (AD) have been reported. Here, we evaluated the CB1R brain profile in an AD mouse model using longitudinal positron emission tomography with an inverse agonist for CB1R, [F-18]FMPEP-d(2). APP/PS1-21 and wild-type (n = 8 in each group) mice were repeatedly imaged between 6 to 15 months of age, accompanied by brain autoradiography, western blot, and CB1R immunohistochemistry with additional mice. [F-18]FMPEP-d(2) positron emission tomography demonstrated lower (p < 0.05) binding ratios in the parietotemporal cortex and hippocampus of APP/PS1-21 mice compared with age-matched wild-type mice. Western blot demonstrated no differences between APP/PS1-21 and wild-type mice in the CB1R abundance, whereas significantly lower (p < 0.05) receptor expression was observed in male than female mice. The results provide the first demonstration that [F-18]FMPEP-d(2) is a promising imaging tool for AD research in terms of CB1R availability, but not expression. This finding may further facilitate the development of novel therapeutic approaches based on endocannabinoid regulation. (C) 2018 The Authors. Published by Elsevier Inc.